Na+/K+-ATPase as a Target of Cardiac Glycosides for the Treatment of SARS-CoV-2 Infection - Souza e Souza, Kauê Francisco Corrêa; Moraes, Bianca Portugal Tavares; Paixão, Izabel Christina Nunes de Palmer; Burth, Patrícia; Silva, Adriana Ribeiro; Gonçalves-de-Albuquerque, Cassiano Felippe (Frontiers in Pharmacology, 2021)
The new coronavirus (SARS-CoV-2), identified the first time in Wuhan, China, overcame epidemic status becoming pandemic. Since its discovery in December 2019, there were countless cases of mortality and morbidity. Several compounds such as chloroquine, hydroxychloroquine, liponavir-ritonavir, and remdesivir have been tested as alternative therapy; however, no effective treatment is recommended by regulatory agencies. Some studies on respiratory non-enveloped viruses such as adenoviruses and rhinovirus and some respiratory enveloped viruses, including human respiratory syncytial viruses, influenza A, parainfluenza, SARS-CoV and SARS-CoV-2 have shown the antiviral activity of cardiac glycosides correlating its effect with Na+, K+ ATPase (NKA) modulation. These compounds are secondary metabolites used to treat patients with cardiac insufficiency because they are the most potent inotropic agents. The effects of cardiac glycosides on NKA is concentration-dependent and may result in the blockage of ionic transport of Na+ and K+ ions or triggers signaling pathways. The antiviral activity of cardiac glycosides is related to cell signaling activation through NKA inhibition. Factor nuclear kappa B (NFκB) seems to be an essential transcription factor for SARS-CoV-2 infection. The NFκB inhibition by cardiac glycosides interferes directly in SARS-CoV-2 yield and inflammatory cytokine production. Besides, cardiac glycosides' antiviral effect is associated with tyrosine kinase (Src) activation and NFκB appears to be regulated by Src. Src is one of the main signaling targets of the NKA α-subunit that modulates other signaling factors that may also impair viral infection. These data suggest that Src-NFκB signaling modulated by NKA plays a crucial role in the inhibition of SARS-CoV-2 infection. Herein, we discuss the antiviral effect of cardiac glycosides on different respiratory viruses, SARS-CoV-2 pathology, cell signaling pathways, and NKA as a possible molecular target for the treatment of COVID-19.